2012
DOI: 10.7728/0203201203
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ethnic Identity in Interventions to Promote Positive Adolescent Development

Abstract: The role of ethnic identity in interventions to promote positive adolescent development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Future studies should test if ethnic identity explains the buffering effect of race attribution when discrimination and prejudice are encountered [68, 69, 70, 71]. Ethnic identity and race attribution has been considered as modifiable factors among African Americans, and may be changed as a consequence of race socialization messages [72].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should test if ethnic identity explains the buffering effect of race attribution when discrimination and prejudice are encountered [68, 69, 70, 71]. Ethnic identity and race attribution has been considered as modifiable factors among African Americans, and may be changed as a consequence of race socialization messages [72].…”
Section: Discussionmentioning
confidence: 99%
“…Steinberg (2001) found that African American and Asian American parents were more likely to use an authoritarian parenting style, whereas European American parents were more likely to use authoritative parenting. Hill et al (2012) found a positive significant relation between authoritarian parenting style and EI in a study with African American children. Chao (1994) found authoritarian parenting style to be associated with poor school achievement for European American students but not for Chinese students.…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, higher scores on the stereotype subscale are indicative of adolescents endorsing positive portrayals of African Americans/Blacks. This scale has been used in other studies examining racial identity (e.g., Belgrave et al, 2004; Breland et al, 2002; Hill et al, 2012). The reliability for the Social subscale is .63, the Appearance subscale = .50, and the Stereotype subscale = .68.…”
Section: Methodsmentioning
confidence: 99%
“…Research using Smith and Brookins’ conceptualization of African American adolescent identity development documents that stronger African cultural values predicted a stronger ethnic identity at post-test for 93 African American adolescent girls participating in an African-centered school-based intervention (Hill et al, 2012). This same study found that African cultural values at pre-test predicted stronger ethnic identity at post-test (Hill et al, 2012).…”
Section: Theological Orientations and Racial/ethnic Identitymentioning
confidence: 99%
See 1 more Smart Citation